KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI SELF CONFIDENCE SISWA - Gemi Susanti; Chairuddin Chairuddin (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
This research is motivated by the low mathematical problem solving ability of students, where most people blame the learning model while there are many factors that influence this, one of which is students' self-confidence. This study aims to determine the differences in students' mathematical communication skills in terms of self-confidence. This type of research is an expost facto study and was conducted at MTs Negeri 2 Kolaka using a sample of 48 students. From the results of the analysis carried out, the average problem-solving ability of students is 50.94 which if converted in table 2 then the value is in the less category. Furthermore, from the inferential analysis obtained > so that it can be concluded that there are significant differences in mathematical problem solving abilities between students with very high, high, medium and low Self Confidence. From the results of further analysis, it was concluded that students with very high self-confidence would have better problem-solving abilities than other students